2018
DOI: 10.1177/0004563218778300
|View full text |Cite
|
Sign up to set email alerts
|

Improved testing for vitamin B12 deficiency: correcting MMA for eGFR reduces the number of patients classified as vitamin B12 deficient

Abstract: Background Methylmalonic acid (MMA) can detect functional vitamin B deficiencies as it accumulates early when intracellular deficits arise. However, impaired clearance of MMA from blood due to decreased glomerular filtration rate (eGFR) also results in elevated plasma MMA concentrations. Alternative to clinical trials, a data mining approach was chosen to quantify and compensate for the effect of decreased eGFR on MMA concentration. Methods Comprehensive data on patient's vitamin B, eGFR and MMA concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In this study, we investigated the cross-sectional association of vitamin B12 and eGFR with MMA. In line with previous studies [2][3][4], we found that MMA levels are associated with vitamin B12 and eGFR and that MMA levels are highest in subjects with a combination of low vitamin B12 levels and impaired renal function. However, we found that only 22% of variation in circulating MMA concentration was explained by vitamin B12, eGFR, age, sex, and SES.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we investigated the cross-sectional association of vitamin B12 and eGFR with MMA. In line with previous studies [2][3][4], we found that MMA levels are associated with vitamin B12 and eGFR and that MMA levels are highest in subjects with a combination of low vitamin B12 levels and impaired renal function. However, we found that only 22% of variation in circulating MMA concentration was explained by vitamin B12, eGFR, age, sex, and SES.…”
Section: Discussionsupporting
confidence: 93%
“…However, concentrations of MMA are not only elevated in vitamin B12 deficiency, but are also known to increase during renal dysfunction [3,4]. Moreover, methylmalonyl-CoA is an intermediate in the metabolism of propionic acid (PA), which is produced as a result of beta-oxidation of odd-chain fatty acids and branchedchain amino acids, metabolism of cholesterol sidechains, and fermentation by colonic microbiota [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these biomarkers increased at early stages of renal impairment with eGFR <100 mL/min/1.73 m 2 . Van Loon et al already reported similar results for plasma MMA at the early stage of renal impairment (≤90 mL/min/1.73 m 2 ) [18]. The impairment of renal function could affect the interpretation of the plasma HCyst and the plasma MMA.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, these biomarkers are not strictly specific for B12 deficiency: vitamin B2, B6, and folate deficiencies can raise the plasma HCyst levels [34][35][36], while dehydration and increased levels of propionic acid can also increase the plasma MMA levels [37]. However, the main impediment is renal impairment as it increases both plasma HCyst and plasma MMA values, leading to an important loss of specificity in this situation [15][16][17][18][38][39][40][41][42]. Fedosov et al proposed an interesting index calculation based on measurements of different biomarkers to suppress the "inherent noise" of each individual marker of B12-deficiency [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation